Effects of N-acetylcysteine on kidney tissue, matrix metalloproteinase-2, irisin and oxidative stress in a diabetes mellitus model - Yalcin, Alper; Gurel, Ali (Taylor & Francis Ltd, 2021)
DM mellitus (DM) is a prevalent chronic disease; diabetic nephropathy (DN) is a primary cause of chronic kidney disease. Oxidation, energy imbalance, and enzyme and cytokine changes contribute to the development and progression of DN. We investigated the possible effects of the antioxidant, N-acetylcysteine (NAC), on kidney morphology, apoptosis, matrix metalloproteinase-2 (MMP2) activity, irisin levels and oxidative stress in an experimental DM model. We used four equal groups of Wistar albino male rats: control, DM, DM + NAC and NAC. Kidney tissues were evaluated for oxidation state, MMP-2, irisin, caspase-3 and histopathology. In the DM group, total oxidant status level, MMP-2 and caspase-3 immunoreactivity were increased, irisin immunoreactivity and total antioxidant status (TAS) were decreased and histological damage was evident. In the DM + NAC group, all changes were significantly improved. NAC exhibited protective effects against DN.
Keywords: Caspase 3; diabetes mellitus; irisin; kidney; matrix metalloproteinase-2; N-acetylcysteine; oxidative stress; rats